Numerical study of crack path by MMCG specimen using M integral (Fracture and Structural Integrity, 2015)
The mixed mode loading configuration occurs in many civil engineering and mechanical applications. In wood material, the study of this problem is very important due to the orthotropic character and the heterogeneity of the material. In order to study the mixed mode loading in wood material, Moutou Pitti et al [1] have proposed a new specimen called Mixed Mode Crack Growth (MMCG). The main goal of this geometry is to propose a decrease of the energy release rate during the crack growth process. In this case, the fracture parameters can be decoupled into Mode I and Mode II in order to determine the impact of time during creep crack test. The present work proposes to study the crack path stability in MMCG specimen for different sizes and thicknesses. The M? integral, combining real and virtual mechanical displacement fields is used in order to separate numerically mode I and mode II in the mixed mode ratio. The stability is shown for the opening mode (Mode I), the shear mode (Mode II), and the mixed mode of 15°, 30°, 45°, 60°, 75° by computing the energy release rate versus the crack length. Finally, it is shown that the MMCG specimen can be reduced in various shape and used for example in small climate chamber in order to perform creep test at different temperature and moisture content levels.
Keywords: Crack stability; MMCG specimen; M integral